The Relationship of Health Worker Knowledge with the Application of Occupational Health and Safety in Community Health Centers - Munika, Evi; Suratmi, Suratmi; Qowi, Nurul Hikmatul (Universitas Muhammadiyah Lamongan, 2023)
Introduction: Occupational Safety and Health (K3) efforts must be carried out in all workplaces, especially those with health risks such as hospitals. Occurrence of work accidents can be caused by many factors, one of which is the behavior of human resources consisting of knowledge, attitudes, and actions. The purpose of this study was to determine whether there is a relationship between knowledge of health workers and the implementation of Occupational Health and Safety (K3) at thecommunity health centerMethods: The research method uses correlation analysis, cross sectional. The population is all health workers at the X Community health center, totaling 59 officers. The sampling technique uses simple random sampling. The sample of this study was 51 health workers. The research method uses analytic correlation and cross sectional. The research data was taken using a questionnaire after tabulating the data which was analyzed using the Spearman Rank test (Rho) with a significance level of p = <0.05.Results: The results of the study showed that out of 51 health workers, almost all of them had high knowledge with good OSH application as many as 46 (93.9%). based on the results of the data above, a statistical test was obtained with a significant value of p sign = 0.725 (p> 0.05). This means that there is no relationship between the knowledge of health workers and the application of occupational health and safety (K3)Conclusion: Based on the research, it is hoped that health workers can implement occupational health and safety properly.